Alpine shrub growth follows bimodal seasonal patterns across biomes – unexpected environmental controls - Svenja Dobbert; Eike Corina Albrecht; Roland Pape; Jörg Löffler (Communications Biology, 2022)
Generalized additive models reveal an unexpected environmental control in shrub growth across biomes.